REVIEW OF IRRATIONAL NUMBERS - Hafnani Hafnani; Rahma Zuhra (Jurnal Natural, 2014)
Study of the set properties is simple and rarely investigated at the Department of Mathematics. This paper examines some set properties on the irrational numbers. The study is about the properties applying to the real numbers which are a complete ordered field. However, the results of this study show that those properties do not imply to the irrational numbers, but the ordered property. The prove of the irrational numberby some examples is demonstrated in this study.